P235 Dual-bronchodilation with once-daily QVA149 in patients with moderate-to-severe COPD: overview of the IGNITE program. (14th November 2013) - Price, D; Mezzi, K; Fedele, MJ; Chen, H; Banerji, D
Abstract : Introduction: In patients with moderate-to-severe chronic obstructive pulmonary disease (COPD) whose symptoms are insufficiently controlled by monotherapy, current treatment strategies recommend the addition of a second bronchodilator with a different mechanism of action. Once-daily QVA149 is a dual bronchodilator combining the long-acting β2 -agonist indacaterol (IND) and long-acting muscarinic antagonist glycopyrronium (GLY). The IGNITE program comprises a series of randomised controlled trials that investigate the efficacy and safety of QVA149 in patients with moderate-to-severe COPD. Methods: This overview includes data from 4 multicentre, double-bind, randomised controlled trials evaluating the effect of QVA149 110/50 μg versus IND 150 μg, GLY 50 μg, tiotropium (TIO) 18 μg (open-label in the SHINE and SPARK studies; blinded in the BLAZE study), salmeterol/fluticasone (SFC) 50/500 μg, and placebo (PBO) in patients with moderate-to-very severe COPD. Outcomes reported here are lung function, transitional dyspnoea index (TDI), health status (via the St George's Respiratory Questionnaire [SGRQ]), and exacerbations over 6 weeks (BLAZE), 26 weeks (SHINE, ILLUMINATE), and 64 weeks (SPARK). Results: Data from 5138 patients were included in this overview. QVA149 provided statistically significant and clinically meaningful bronchodilation (p < 0.001) that was sustained throughout the treatment periods versus all comparators in all studies. QVA149 provided superior benefits versus TIO, SFC, and PBO with respect to TDI score in BLAZE and ILLUMINATE studies. At Week 64, QVA149 significantly improved SGRQ score (p≤0.001) and significantly lowered the rate of all exacerbations compared with GLY and TIO in the SPARK study (Table). In addition, QVA149 reduced the rate of all exacerbations by 31% and significantly delayed the time to first exacerbation versus SFC in the ILLUMINATE trial. Conclusion: The results from the IGNITE trials demonstrate that superior improvements in lung function with once-daily QVA149 translate into meaningful therapeutic outcomes for patients with COPD as demonstrated by improved lung function, dyspnoea, health status, and reduced exacerbations.